Vitamin D status, diabetes mellitus and coronary artery disease in patients undergoing coronary angiography. (July 2016) - Nardin, Matteo; Verdoia, Monica; Schaffer, Alon; Barbieri, Lucia; Marino, Paolo; De Luca, Giuseppe; ,
Abstract: Background and aims: Growing attention has been addressed to the cardiovascular effects of vitamin D, in order to prevent the vascular wall degeneration and the progression of atherosclerosis. Diabetes mellitus is an established risk factor for coronary artery disease, where the enhanced pro-inflammatory and pro-thrombotic status could render even more important the athero-protective effects of vitamin D. Therefore, we aimed to evaluate the impact of diabetes on vitamin D levels and its relationship with the extent of CAD. Methods: Consecutive patients undergoing non urgent coronary angiography were included. Admission samples were collected for vitamin D levels assessment. Significant coronary artery disease was defined as at least 1 vessel stenosis >50%, severe coronary artery disease as left main and/or trivessel disease, as evaluated by quantitative coronary angiography. Results: Patients included were 1859, among them 641 were diabetics (34.5%). Diabetic patients displayed older age, higher rate of renal failure, previous cardiovascular events, hypercholesterolemia, hypertension, glycaemia, HbA1c, creatinine, uric acid ( p < 0.001, respectively). Lower levels of haemoglobin, total cholesterol, high and low density lipoprotein cholesterol ( p < 0.001) were found in diabetics. Diabetic patients displayed significantly lower levels of vitamin D ( p = 0.003), however diabetes did not emerge as an independent predictor of hypovitaminosis-D (adjusted OR [95% CI] = 0.95[0.72, 1.26], p = 0.72). In diabetics, lower vitamin D levels were associated to female gender ( p = 0.003), glucose control and lower haemoglobin levels ( p < 0.001). Lower levels of vitamin D were related with the prevalence (adjusted OR [95% CI] = 1.54[1.12–2.12], p = 0.008) and severity (adjusted OR [95% CI] = 1.28[1.014–1.621], p = 0.038) of coronary artery disease. Conclusions: The present study shows that diabetes mellitus is not an independent predictor of hypovitaminosis-D. However, diabetic patients showed lower vitamin D levels that were independently associated with an increased prevalence and severity of coronary artery disease. Highlights: We evaluated the relationship between 25-OH D, diabetes and coronary artery disease (CAD). We included 1859 patients, with 641 diabetics, undergoing coronary angiography. Diabetes mellitus did not emerge as an independent predictor of hypovitaminosis D. Lower levels of vitamin D significantly correlated with the prevalence of CAD. Lower levels of vitamin D significantly correlated with the severity of CAD.